Synthesis of Indolostilbenes via FeCl3-promoted Oxidative Cyclisation and their Biological Effects on NG108-15 Cell Viability and H2O2-induced Cytotoxicity - Mohamad Nurul Azmi (Tanjung Malim, 2021)
Synthesis of Indolostilbenes via FeCl3-promoted Oxidative Cyclisation and their Biological Effects on NG108-15 Cell Viability and H2O2-induced Cytotoxicity by Mohamad Nurul Azmi